Sierra Leone : Poverty Reduction Strategy Paper: Progress Report, 2008-10. (IMF Staff Country Reports; Country Report, 2011)
Attention was especially focused on infrastructural development and the implementation of the free health care program. Another key poverty reducing strategy is the Smallholder Commercialisation Scheme. A robust monitoring and evaluation system has been established. Inadequate domestic capacity negative attitudes and fraudulent behavior toward execution of public contracts, delayed donor disbursement of funds for public works, and limited intra- and intersectoral coordination has been limiting factors. Developing a comprehensive policy framework to regulate behavior of contractors and ensuring timely release of donor funds for projects is needed.